Processing and characteristics of transparent Gd3TaO7 polycrystalline ceramics. Issue 5 (4th December 2017) - Chen, Ching‐Fong; Synowicki, Ron A.; Brand, Michael J.; Tegtmeier, Eric L.; Montalvo, J. D.; Ivy, Jacob; Brennecka, Geoff L.; Seeley, Zach; Cherepy, Nerine J.; Payne, Steven A.
Abstract: Transparent polycrystalline Gd3 TaO7 ceramics were successfully developed. A sol‐gel process was used to synthesize Gd3 TaO7 powder with a uniform composition and an estimated average particle size of 100 nm. Simultaneous thermal gravimetric analysis and differential thermal analysis (TGA/DTA) was used to identify the decomposition sequence as a function of temperature for the as‐synthesized sol‐gel powders. Crystallization was confirmed by X‐ray diffraction (XRD) and a single phase was achieved by calcining at 1000°C. The calcined powders were hot‐pressed at 1400°C to achieve >96% theoretical density with closed pore structure followed by a hot isostatic pressing at 1400°C at 207 MPa to achieve a fully dense structure. Microstructural characterization shows a uniform grain size distribution with an average grain size of about 7 μm. In‐line transmission measurements revealed high transparency in the red and infrared. Thermal conductivity was measured to be >1.6 W/mK at room temperature, decreasing to 1.3 W/mK by 500°C. Dielectric properties remain stable with relative permittivity values just above 200 and loss tangents <0.005 up to 350°C.